Photographic and angiographic characterization of the retina of Kenyan children with severe malaria. - Hero, M; Harding, S; Riva, C; Winstanley, P; Peshu, N; Marsh, K (1997)
OBJECTIVE: To investigate retinal lesions in children with severe falciparum malaria. METHODS: Color photography and fluorescein angiography were performed in consecutive children admitted to a pediatric high-dependency unit in Kenya during 1 malaria season. The presence and category of retinal lesion was compared with disease severity, clinical outcome, anemia, lactic acidosis, and parasite count. RESULTS: Twenty-six patients with cerebral malaria and 14 patients who were prostrate were studied. Thirty-one of the patients had clinical features of ocular disease, including round, flame-shaped, and white-centered hemorrhages; peripheral and foveal retinal opacification; peripheral vascular occlusion; venous dilation; disc edema with hyperemia; and arterial pulsatility. Of 8 patients with retinal opacification, only 2 showed small, infrequent zones of capillary nonperfusion on fluorescein angiography; the leakage of dye at sites of opacification was not seen. Retinal opacification was significantly associated with a higher parasite count (P < .02). White-centered hemorrhages were significantly associated with a higher parasite count (P < .05), severe disease (p < .05), and severe anemia (P < .02). CONCLUSIONS: The blood-retina barrier and retinal vascular flow remain substantially normal despite widespread pathological features. Retinal features in children with severe malaria are consistent with cellular hypoxia, nutritional deficiency, or both rather than with vascular occlusion; they support the concept of metabolic steal by parasites.